Gaining Sustainable Performance through Risk Management System: Dealing with Uncertainty in Islamic Insurance Companies - Addini, Sabila Nur; Berakon, Izra; Muhammad, Nor Nabilla (Muslim Business and Economics Review, 2024)
This study investigates how the halal business process sustains company performance by examining the effect of premiums, claims, operating costs, investment income, and risk-based capital on the profitability of Islamic insurance in Indonesia. In particular, the risk management system is key to demonstating how Islamic insurance companies restrain risks to gain profits, considering that the basic concept of Islamic insurance is the risk sharing approach. Moreover, to provide research novelty and originality, the authors expand the research framework to include the interactions of the company's risk management system to test the influence of investment income and risk-based capital on profitability. The overall population comprised all Islamic insurance companies in Indonesia, but samples were restricted to life insurance businesses registered with the Indonesian Islamic Insurance Association for 2018-2022. The authors were left with a sample of 13 companies after using a non-probability approach with a purposive sampling technique. The data was analyzed by STATA 17 on four gradual statistical procedures: Panel Data Regression Analysis, Moderated Regression Analysis, Robustness Test Analysis, and Content Analysis. The results demonstrate that the premiums, claims, and investment income have no significant effect on company profitability. Meanwhile, operational costs and risk-based capital have a significant effect on profitability performance. Furthermore, enterprise risk management successfully acts as a moderating variable. Based on findings, the authors strongly recommend that Islamic insurance companies effectively implement enterprise risk management in dealing with uncertain circumstances for the real business process.